2004
DOI: 10.1029/2004jd004532
|View full text |Cite
|
Sign up to set email alerts
|

Estimates of net CO2 flux by application of equilibrium boundary layer concepts to CO2 and water vapor measurements from a tall tower

Abstract: [1] Convective turbulence within the atmospheric boundary layer (ABL) and movement of the ABL over the surface results in a large spatial (10 4 -10 5 km 2 ) integration of surface fluxes that affects the CO 2 and water vapor mixing ratios. We apply quasi-equilibrium concepts for the terrestrial ABL to measurements of CO 2 and water vapor made within the ABL from a tall tower (396 m) in Wisconsin. We suppose that CO 2 and water vapor mixing ratios in the ABL approach an equilibrium on timescales longer than a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
103
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(106 citation statements)
references
References 50 publications
3
103
0
Order By: Relevance
“…Our vision for the future includes: (1) identifying and funding critical new locations for FLUXNET towers in poorly studied biomes, for instance in tropical croplands; (2) nesting EC towers within the regional footprints of tall towers that sample the CO 2 concentration of the planetary boundary layer (Helliker et al, 2004) to assist upscaling; (3) linking EC towers effectively with the atmospheric column CO 2 measurements generated by the satellites OCO and GOSAT, expected from late 2009 (Feng et al, 2008); (4) continued linkage to optical products from remote sensing, as these provide critical information on canopy structure and phenology (Demarty et al, 2007); (5) use of plant functional traits database to identify more realistic priors and to validate posteriors in the data assimilation process (Luyssaert et al, 2007). Full exploitation of this vision is dependent on model-data fusion.…”
Section: Discussionmentioning
confidence: 99%
“…Our vision for the future includes: (1) identifying and funding critical new locations for FLUXNET towers in poorly studied biomes, for instance in tropical croplands; (2) nesting EC towers within the regional footprints of tall towers that sample the CO 2 concentration of the planetary boundary layer (Helliker et al, 2004) to assist upscaling; (3) linking EC towers effectively with the atmospheric column CO 2 measurements generated by the satellites OCO and GOSAT, expected from late 2009 (Feng et al, 2008); (4) continued linkage to optical products from remote sensing, as these provide critical information on canopy structure and phenology (Demarty et al, 2007); (5) use of plant functional traits database to identify more realistic priors and to validate posteriors in the data assimilation process (Luyssaert et al, 2007). Full exploitation of this vision is dependent on model-data fusion.…”
Section: Discussionmentioning
confidence: 99%
“…Terrestrial NPP has been showed to play a central role in determining the local and global CO2 content of the atmosphere at temporal scales spanning hours [8] to epochs [9].…”
Section: Introductionmentioning
confidence: 99%
“…In order to estimate CO 2 exchange over such wide areas, it is necessary to determine the atmospheric CO 2 concentration on a regional scale, broadly defined as 10 4 to 10 6 km 2 (Helliker et al 2004). To meet this requirement, tall towers have been used as monitoring sites since the 1990s (Bakwin et al 1995(Bakwin et al , 1998(Bakwin et al , 2004Haszpra 1999).…”
Section: Introductionmentioning
confidence: 99%